2007
DOI: 10.1016/j.neulet.2006.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the physiological actions of the triphasic EMG pattern by a dynamic recurrent neural network

Abstract: Triphasic electromyographic (EMG) patterns with a sequence of activity in agonist (AG1), antagonist (ANT) and again in agonist (AG2) muscles are characteristic of ballistic movements. They have been studied in terms of rectangular pulse-width or pulse-height modulation. In order to take into account the complexity of the EMG signal within the bursts, we used a dynamic recurrent neural network (DRNN) for the identification of this pattern in subjects performing fast elbow flexion movements. Biceps and triceps E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…We have also demonstrated that the DRNN is able to reproduce the major parameters of human limb kinematics such as: (1) fast drawing of complex figure by the upper limb , Draye et al 1997, (2) whole-body straightening (Draye et al 2002), (3) lower limb movement in human locomotion (Cheron et al 2003;Cheron et al 2006) and (4) pointing ballistic movement (Cheron et al 2007). In all of these experimental situations we have found that the attractor states reached through DRNN learning correspond to biologically interpretable solutions (Cheron et al 2007). It was recently demonstrated that neural network with continuous attractors might symbolically represent context-dependent retrieval of short-term memory from long-term memory in the brain (Tsuboshita and Okamoto, 2007).…”
Section: Multiple Emg Signals As a Final Output Controllermentioning
confidence: 71%
See 2 more Smart Citations
“…We have also demonstrated that the DRNN is able to reproduce the major parameters of human limb kinematics such as: (1) fast drawing of complex figure by the upper limb , Draye et al 1997, (2) whole-body straightening (Draye et al 2002), (3) lower limb movement in human locomotion (Cheron et al 2003;Cheron et al 2006) and (4) pointing ballistic movement (Cheron et al 2007). In all of these experimental situations we have found that the attractor states reached through DRNN learning correspond to biologically interpretable solutions (Cheron et al 2007). It was recently demonstrated that neural network with continuous attractors might symbolically represent context-dependent retrieval of short-term memory from long-term memory in the brain (Tsuboshita and Okamoto, 2007).…”
Section: Multiple Emg Signals As a Final Output Controllermentioning
confidence: 71%
“…This rhythmical organization could be viewed as resulting from a motor binding process (Sanes and Truccolo, 2003) supported by the synchronization of cortical neurons forming functional assemblies in the premotor and primary motor cortex (Jackson et al 2003;Hatsopoulos et al 2003Hatsopoulos et al , 2007Rubino et al 2006). Moreover, the timing of the antagonist EMG burst is pre-programmed by the cerebellum and our DRNN has been able to learn and reproduce such aspect of motor control (Cheron et al 2007). This will permit to use the antagonist EMG burst to stop adequately a prosthetic movement.…”
Section: Multiple Emg Signals As a Final Output Controllermentioning
confidence: 93%
See 1 more Smart Citation
“…We have to note that in this case the kinematics data are given by the position signals of the index finger (the outputs of the DRNN were the vertical and the horizontal position of the index). In a second set of studies (Cheron et al, 2007) the subjects were asked to perform 'as fast as possible' flexion movements of the elbow in the vertical plane. In this case the angular acceleration of the elbow was used as the output.…”
Section: Emg and Movements Recordingsmentioning
confidence: 99%
“…DRNNs are recognized as universal approximators of dynamical systems (Kuan and Hornik, 1991; Doya, 1996; Yi et al, 2006; Tani et al, 2008; Bicho et al, 2011; Laje and Buonomano, 2013) and the attractor states reached through DRNN learning of EMG-to-kinematic patterns correspond to biologically interpretable solutions (Cheron et al, 1996, 2003, 2006, 2007, 2011; Song and Tong, 2005; Liu and Buonomano, 2009). After the learning phase, the identification performed by the DRNN offers a dynamic memory which has been used, for example, to recognize the physiological preferred direction of action for the studied muscles (Cheron et al, 1996, 2003, 2006, 2007).…”
Section: Introductionmentioning
confidence: 99%